Assessment of effectiveness of CFRP repaired RC beams under different damage levels based on flexural stiffness - Fayyadh, M.M.; Razak, Hashim Abdul (Elsevier, 2012)
This paper presents a study to determine the effectiveness of Carbon Fiber Reinforced Polymer (CFRP) sheets as a flexural repair system for Reinforced Concrete (RC) beams. The effectiveness of these sheets is ascertained by monitoring the flexural stiffness recovery. Experimental work is conducted on scaled beams where four beams are used as the datum. The first beam is without CFRP sheets, the second is a repaired beam after pre-damaged under design load limit, whilst the third is a repaired beam after pre-damaged under steel yield load limit, and the fourth is a repaired beam after pre-damaged under ultimate load. Comparisons are made based on the flexural stiffness recovery, crack patterns, load capacity, and failure modes of the beams. The study validates the ability of the flexural stiffness change in order to monitor the effect of the damage as well as the effectiveness of the repair on stiffness recovery. The results prove the effectiveness of the CFRP sheets as a repair technique which increases the flexural stiffness and the ultimate load capacity whatever the pre-repair damage levels. In addition, this study indicates the ability of re-repairing the beams in the case of CFRP debonding. The failure modes are controlled by the pre-repair damage flexural crack wherein it causes the CFRP debonding.